(untitled) (IITM Journal of Business Studies, 2024)
The paper is an attempt to assess the impact of working capital management on liquidity and profitability (ROI) of the company and to establish the linear relationship between liquidity and profitability with the help of multi regression model. For assessing the impact, a 13 year period has been considered. The study is based on secondary data collected from published annual reports of the refinery which are analyzed with the help of correlation and ANOVA test. The study focuses on the factors which are responsible for changing the working capital of the refinery which as a result influences the profitability of the refinery. The study shows the result of different independent variables on profitability of the refinery.